Penentuan Strategi Saluran Distribusi Berdasarkan Karakteristik Produk Sukses - Isnaini Nurisusilawati; S Subagyo (Faculty of Engineering, Universitas Gadjah Mada, 2016)
This research was done to determine the distribution channel strategy based on characteristics of successful products. Totaling 100 products from 15 types of product categories were used as a research object. Independent variables consisted of product characteristic variables and distribution channel variable. Product characteristic variables consisted of price, safety, feature, product performance, service, convenience, brand, and design. Coverage was used as adistribution channel variable and market share as a dependent variable. Ordinary Kano and Modified Kano were used to construct some mathematical models. Each model then was evaluated with coefficient determination test. The mathematical model constructed in this study has R2 value 16,26%. Coverage included in one-dimensional requirement which means adding value to coverage variable will linearly increase market share. Keyword: channel distribution strategy, product characteristics, Kano model, mathematical model.